2022
DOI: 10.1186/s40729-022-00410-w
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of patient’s perception and knowledge of dental implants in Japan

Abstract: Background This study aimed to collect data regarding patient perception and knowledge of dental implants. It was conducted with the hope that the data would provide dental professionals and policymakers with a better understanding of ways to promote implant therapy. Methods  An anonymous online survey with 10 questions was distributed through 12 dental offices in Tokyo and provincial cities in Japan to assess patient perception and knowledge of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…At the same time, the majority of them (44.3% of participants) stated that the high cost of dental implants is the reason they do not choose them as a treatment option. This finding is consistent with the three studies mentioned in the dental implant literature [16][17][18]. The majority of them (54.6%) are willing to learn more about dental implants.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, the majority of them (44.3% of participants) stated that the high cost of dental implants is the reason they do not choose them as a treatment option. This finding is consistent with the three studies mentioned in the dental implant literature [16][17][18]. The majority of them (54.6%) are willing to learn more about dental implants.…”
Section: Discussionsupporting
confidence: 91%
“…These were comparable to the studies conducted in past. [16,17] We found that majority of the cases 90 (56.3%) were females and 70 (43.7%) were males. There were 101 (63.1%) patients had rural residency and 59 (36.9%) were from urban area.…”
Section: Discussionmentioning
confidence: 64%
“…Also, their patients believed that the purpose of dental implants was to avoid dentures and improve chewing function. Their primary concerns about dental implants were the cost and longevity, and 61% of patients without implants did not know that bone grafts may be required [22]. Whereas the knowledge related to dental implants could have been more satisfactory, only 4.5% showed good knowledge.…”
Section: Discussionmentioning
confidence: 99%